2020
DOI: 10.1155/2020/3109612
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Sensitivity of Mechanical Properties of Cement Asphalt Mortar with Nanoparticles

Abstract: Cement asphalt mortar (CAM) in high-speed lines is subjected to varying environmental conditions, which lead to the deterioration of CAM. e nanoparticles of nano-SiO 2 and nano-TiO 2 are added to improve the performance of CAM, and the temperature sensitivity of CAM with nanoparticles is primarily studied in this paper. e flexural strength and compressive strength of CAM with and without nano-SiO 2 and nano-TiO 2 were measured and compared to study the effect of nanoparticles on the performance of CAM subjecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…On the other hand, the cementitious phase in the CEBM was dispersed within the emulsified bitumen. The cement hydration consumed a portion of the water that occupies the micro air void spaces between the emulsified bitumen and aggregate, which had a stiffening effect on emulsified bitumen [ 43 , 46 ]. The hydration products of the aggregate and cement, the skeleton function of the cement, and the encapsulation and adhesion function of the emulsified bitumen complement each other, and together with the hydration products of cement interweave with demulsified bitumen to enhance the overall stability and form the strength of CEBM.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the cementitious phase in the CEBM was dispersed within the emulsified bitumen. The cement hydration consumed a portion of the water that occupies the micro air void spaces between the emulsified bitumen and aggregate, which had a stiffening effect on emulsified bitumen [ 43 , 46 ]. The hydration products of the aggregate and cement, the skeleton function of the cement, and the encapsulation and adhesion function of the emulsified bitumen complement each other, and together with the hydration products of cement interweave with demulsified bitumen to enhance the overall stability and form the strength of CEBM.…”
Section: Resultsmentioning
confidence: 99%
“…Nanoparticles are among the useful additives with promising influence in improving the performance properties of CBM and bituminous mixtures. Nanoparticles such as nano-SiO 2 and nano-TiO 2 are broadly used to enhance the strength and durability of CBMs [78,79]. Previous researches showed that nanoparticles in CBMs could react with Ca(OH) 2 crystals and generate more C-S-H gel, which occupies the void spaces and enhances the density of the interfacial transition zone [80][81][82].…”
Section: Use Of Additives In Ca Mortar Productionmentioning
confidence: 99%
“…Hasaninia and Haddadi investigated the rutting and fatigue damage of asphalt caused by nano-SiO 2 and found the correlation between modified binder and the engineering performance of asphalt mixture [13]. Wu et al explored the temperature sensitivity of nanoparticles to cement mortar, the influence of nano-SiO 2 on the strength of cement asphalt mortar, and the performance of nano-SiO 2 cement asphalt mortar at different temperatures [14]. Rezaei et al modified asphalt with nano-SiO 2 and SBS polymer and analyzed its hightemperature performance [15].…”
Section: Introductionmentioning
confidence: 99%